Come away [videorecording (DVD)] - Oyelowo, David; Chancellor, Anna; Mbatha-Raw, Gugu, 1983-; Jolie, Angelina, 1975- (Relativity Media LLC, 2020)
In this imaginative origin story of two of the most beloved characters in literature, Peter Pan and Alice in Wonderland, eight-year-old Alice, her mischievous brother Peter, and their brilliant older sibling David let their imaginations run wild one blissful summer in the English countryside, encouraged by their parents Jack and Rose.